DAMPAK PSIKOLOGI KARYAWAN DAN TARIF PAJAK TERHADAP MOTIVASI KERJA KARYAWAN PJLP (Studi Kasus Pada Kebijakan Pemototongan PPh Pasal 21 Di RSUD Pasar Minggu) - Ika agustina; Retno Rizki; Yandi Asmana (LPPM Sekolah Tinggi Ilmu Ekonomi Ganesha, 2026)
This study aims to analyze the influence of employee psychology and tax rates on the work motivation of Individual Service Providers (PJLP) in relation to the year-end Article 21 income tax withholding policy implemented at RSUD Pasar Minggu, South Jakarta. The research was conducted in response to employees’ perceptions of unfairness, anxiety, and declining motivation due to lump-sum tax deductions applied without prior explanation. A quantitative descriptive method with an associative design was employed, and data were collected through questionnaires distributed to PJLP employees. The analysis included validity and reliability testing, normality testing, heteroscedasticity testing, and multiple linear regression, with hypothesis testing performed using t-tests and F-tests. The findings reveal that: (1) employee psychology significantly affects work motivation, where higher perceptions of fairness and transparency lead to increased motivation; (2) tax rates have a significant negative effect on motivation when higher deductions are imposed without adequate socialization; and (3) employee psychology and tax rates simultaneously exert a significant influence on work motivation. The study concludes that the year-end withholding policy impacts both the financial and psychological aspects of employees. Therefore, enhanced transparency, communication, and socialization are essential to ensure that tax deductions are fairly understood and accepted by employees.